A broadband coplanar waveguide to rectangular waveguide power divider using a slot. Issue 2 (4th September 2012) - Fang, Ruei‐Ying; Wang, Cheng‐Tze; Wang, Chun‐Long
Abstract In this article, a broadband coplanar waveguide (CPW) to rectangular waveguide power divider using the dipole slot is proposed. The power divider consists of an input CPW port and two output rectangular waveguide ports. The CPW to rectangular waveguide power divider using the dipole slot has a return loss larger than 15 dB and an insertion loss equal to 3.08–3.27 dB in the whole X‐band (8.2–12.4 GHz). Furthermore, to broaden the bandwidth, the dipole slot is replaced by the bow‐tie slot. The CPW to rectangular waveguide power divider using the bow‐tie slot yields a return loss larger than 16 dB and an insertion loss equal to 3.05–3.29 dB from 8 to 13 GHz, which exceeds the X‐band. To verify our design, power dividers that use the dipole slot or the bow‐tie slot are fabricated and measured. The measurement results of both power dividers are in good agreement with the simulation results. © 2012 Wiley Periodicals, Inc. Int J RF and Microwave CAE, 2013.